INTEGRATION OF EDUCATION IN HIGHER EDUCATION: AIMING TO IMPROVE THE EDUCATION AND DEVELOPMENT OF STUDENTS - Faisal, Faisal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore the integration of Tariqoh in higher education as an effort to improve the quality of education and student development. Tariqoh, as a religious and spiritual approach, is considered to have the potential to have a positive impact on the formation of students' character, ethics and understanding of life in the academic environment. The research methodology used is a qualitative methodology with case study research. The data collection techniques used in this research are interview, observation and documentation techniques. The results of the research show 1) That Tariqoh is a routine activity that is part of the Student Activities Unit and is under the supervision of the MATAN Organization. 2) The MATAN organization is the core organization for implementing Tariqoh at Nurul Jadid University and is an effort to continue the preaching of the Prophet Muhammad S/A.W. 3) The implementation of Tariqoh is an effort to improve the quality of students in the religious field so that when students graduate or leave the university environment, students are able to accompany and even lead religious activities in the community. The integration of Tariqoh in the Islamic higher education environment is expected to be able to maintain Islamic values in the era of modernization.